DESAIN DAN SIMULASI SMART OFFICE BERBASIS INTERNET OF THINGS (IOT) - Ryan Eka Pratama; Eka Purwa Laksana (FAKULTAS TEKNIK UNIVERSITAS BUDI LUHUR, 2021)
In this research, an IoT-based Smart Office network simulation has been built which consists of Smart Devices such as automatic doors, CCTV cameras, Fire Sprinkles, Solar Panels, automatic lights and Air Conditioners (AC). Each Smart Device has Conditions that function as automation which aims to minimize the interaction between the user and the device directly. Smart Devices can be accessed and monitored using Laptops in the office and Smartphones in different locations. The testing method in this study uses the Ping Test method and data analysis refers to the TIPHON standard for the Delay and Packet Loss parameters. The simulation was carried out using Cisco Packet Tracer software version 7.3.1. The results obtained indicate that the Smart Device can be simulated according to the predetermined conditions. The results of the connection test on the Smart Office network show that the delay with the highest value is found on the RFID Reader device at 06:00 – 08:00 WIB and the Motion Detector device at 14:00-16:00 WIB. Both devices scored 47.2ms. The delay with the lowest value is found on the AC Office device at 06:00-08:00 WIB with a value of 24.2ms. This value is in the Very Good category with an Index value of 4. The results of the connection test on the Smart Office network for the Packet Loss parameter show that all Smart Devices get a value of 0% in each test time. This value is included in the Very Good category with an Index value of 4.